Analysis of Consumer Perception and Preferences for Affordable Green Products in Traditional Markets (Study at Simpang Limun Market, Medan) - Elisabeth Marlina Sari Lintong (Yayasan Literasi Sains Indonesia, 2025)
The growing concern for environmental issues and public awareness of nature conservation have driven the emergence of eco-friendly products with minimal environmental impact. However, the perception that eco-friendly products are expensive remains a barrier, particularly for middle- to lower-income consumers. This study aims to examine consumer perceptions and preferences toward affordable eco-friendly products in traditional markets, focusing on Simpang Limun Market, Medan, using a quantitative survey approach. Data were collected in December 2024 from 97 respondents using a pre-developed questionnaire. The results indicate that although awareness of eco-friendly products is relatively high, price remains the primary factor influencing purchasing decisions. Consumers in traditional markets tend to prefer affordable eco-friendly products, supported by direct interaction with sellers and competitive pricing. Consumer perceptions and preferences regarding affordable eco-friendly products have a positive and significant influence on consumer attitudes and behavior. On the other hand, driving and inhibiting factors, while positive, do not show a significant influence. These findings offer valuable guidance for producers and marketers to improve the accessibility and acceptance of eco-friendly products through competitive pricing strategies and more intensive consumer education.